Relationship between muscle volume and strength asymmetry in elite athletes: investigation of the quadriceps femoris and hamstring muscles - Bollinger, R.; Bubeck, D.; Sialis, I.; Kramer, D.; Lehmann, E.; Alt, W. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to examine the relationship between muscle volume asymmetries and strength asymmetries of the lower extremity. 26 highly trained athletes underwent isometric and isokinetic strength tests at different speeds (60, 180, 0 °/s) and magnetic resonance imaging (MRI) to analyse quadriceps femoris and hamstring muscle volume. Pearson`s correlation coefficients revealed significant correlations between both the quadriceps volume asymmetries and the maximum knee extension asymmetries (r = .60 to r = .72) as well as the hamstring volume asymmetries and the maximum knee flexion asymmetries (r = .39 to r = .52). It is assumed that bilateral differences in muscle volume in part explain the existence of strength asymmetries and that unilateral resistance training of the lower extremity could reduce strength asymmetries by increasing muscle size